Modulation of the thermosensory system by oxytocin - Zayan, Ugo; Caccialupi Da Prato, Laura; Muscatelli, Françoise; Matarazzo, Valéry (Frontiers in Molecular Neuroscience, 2023)
Oxytocin (OT) is a neurohormone involved early in neurodevelopment and implicated in multiple functions, including sensory modulation. Evidence of such modulation has been observed for different sensory modalities in both healthy and pathological conditions. This review summarizes the pleiotropic modulation that OT can exercise on one - often overlooked - sensory system: thermosensation. This system allows us to sense temperature variations and compensate for them to maintain a stable core body temperature. OT modulates autonomic and behavioral mechanisms underlying thermoregulation at both central and peripheral levels. Hypo- or hypersensitivity for different sensory modalities, including thermosensitivity, is a common feature in autism spectrum disorder (ASD), recapitulated in several ASD mouse models. These sensory dysregulations occur early in post-natal development and are correlated with dysregulation of the oxytocinergic system. Here we discuss the potential link between thermosensory atypia and the dysregulation of the oxytocinergic system in ASD.